2021
DOI: 10.3390/act10060107
|View full text |Cite
|
Sign up to set email alerts
|

Sensing, Actuation, and Control of the SmartX Prototype Morphing Wing in the Wind Tunnel

Abstract: This paper presents a study on trailing edge deflection estimation for the SmartX camber morphing wing demonstrator. This demonstrator integrates the technologies of smart sensing, smart actuation and smart controls using a six module distributed morphing concept. The morphing sequence is brought about by two actuators present at both ends of each of the morphing modules. The deflection estimation is carried out by interrogating optical fibers that are bonded on to the wing’s inner surface. A novel application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Additional studies using this sensing approach have shown that the total number of fibres required can essentially be reduced to seven for the SmartX wing without compromising on the accuracy; i.e., one each for the six morphing modules [27] (chordwise) and one for the wing [28] (spanwise). In short, a single morphing surface requires just one fibre containing four FBG sensors [29]. Furthermore, once properly calibrated, this fibre-optic methodology is capable of identifying the position and magnitude of an external load acting on the morphing surfaces [30].…”
Section: Fibre-optic Shape Sensingmentioning
confidence: 99%
“…Additional studies using this sensing approach have shown that the total number of fibres required can essentially be reduced to seven for the SmartX wing without compromising on the accuracy; i.e., one each for the six morphing modules [27] (chordwise) and one for the wing [28] (spanwise). In short, a single morphing surface requires just one fibre containing four FBG sensors [29]. Furthermore, once properly calibrated, this fibre-optic methodology is capable of identifying the position and magnitude of an external load acting on the morphing surfaces [30].…”
Section: Fibre-optic Shape Sensingmentioning
confidence: 99%
“…In this paper, we investigate the deformed shape estimation using optical fibre technology with a quasi-distributed Fibre Bragg Grating (FBG) sensor layout. This work is an extension of the successful demonstration of the potential of this method on a 1-dimensional case involving a cantilever beam [ 21 ], a 2-dimensional load monitoring study on a cantilever plate [ 22 ] and in a composite wing prototype [ 23 ]. A morphing wing-section model (with similar shape to the SmartX prototype) is used for the experimental study.…”
Section: Introductionmentioning
confidence: 99%